Imagination, creativity, and responsible management in the fourth industrial revolution - Fields, Ziska, 1970-; Bucher, Julien, 1985-; Weller, Anja, 1985- (Business Science Reference, 2019)
"This book explores how human imagination and creativity can be used to develop responsible and sustainable management in the fourth industrial revolution to develop more opportunities for humans to thrive"--